Caractérisation Des Risques Hydroclimatiques Dans Le Bassin Versant De L’Ouémé A L’exutoire De Bétérou Au Bénin (Afrique De L’ouest) - Olivier, Koudamiloro; Wilfrid, Vissin Expédit; Jean-Marie, Dipama (European Scientific Journal, ESJ, 2017)
In the catchment area of Ouémé with Bétérou the extreme climatic phenomena lead to risks hydroclimatic which can create, for lack of an adequate management, massive migrations of populations, ecological disasters as well as shortages of food, of energy, of essential water and other goods. The work aims to study the risks hydroclimatic in the catchment area of Ouémé to the discharge system of Bétérou. To achieve this goal, from the climatological data (height daily and monthly of rains, temperatures, ETP) over 1965 to 2012 period are obtained at the National Direction of the Meteorology (DNM) of Cotonou. The hydrological data made up of the daily outputs of the Ouémé river to the discharge system of Bétérou, over 1965-2012 period are extracted from the data base of DGWater. The diagnostic methods of the climate used are primarily statistical and relate to the frequential analysis and the calculation of the indices of dryness. The analysis of the results shows that in the catchment area of Ouémé with Bétérou analyzes compared of the three indices of weather dryness (Decile, RDI and the SPI), that the basin known over the period of 1965 to 1990 three years very dry (1981, 1982 and 1987) and a year close to the extreme dryness (1983). It also arises that index PDSI made it possible to identify the various periods of dryness recorded in the middle In the basin, the recurrences of the rains and maximum us flows are also 2, 5, 10, 20, 50, 100 and 200 years and make it possible to say that the area can be in prey of exceptional flood which can likely involve floods which will not be without consequences on the local development.